Abduction of a child by one looking for parents, problems of qualifying a crime and responsibility for such actions - Tienieshev, Viacheslav; Kotys, Viktoriia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The article examines the gaps in the legislation of Ukraine regarding the qualification of the crime of abduction of a child by one of the parents and the execution of a court decision on the removal of a child in case of his refusal to return to his legal place of residence. Possible means for prevention and effective response to cases of imbalance of interests between parents regarding the place of residence of a joint child are identified. The experience of foreign states and the norms of international documents on responsibility for the abduction of a child are analyzed. The necessity of legislative regulation of this problem is studied and the consequences of ignoring it are covered. In Ukraine there is no culture of civilized divorce and joint custody, it often comes to upsetting the balance of interests between parents, they take a selfish position, in which the child suffers primarily, which becomes a "bargaining chip" and a means of mutual parental revenge. Ignoring the need for a clear and effective legal solution to this issue leads to a decrease in the birth rate, and as a consequence, to the aging of the Ukrainian nation.